A dithiocarbamate-based H2O2-responsive prodrug for combinational chemotherapy and oxidative stress amplification therapy. Issue 92 (1st November 2019) - Pan, Qingqing; Zhang, Boya; Peng, Xinyu; Wan, Shiyu; Luo, Kui; Gao, Wenxia; Pu, Yuji; He, Bin
Abstract : A H2 O2 -responsive dithiocarbamate-based prodrug was designed for combinational cancer therapy, showing superior anticancer efficacy and biostability to disulfiram. Abstract : Here, we report the rational design of a H2 O2 -responsive diethyldithiocarbamate (DTC)-based prodrug, which chelated Cu(ii ) to form Cu(DTC)2 with a high anticancer activity in a tumor-microenvironment and induced oxidative stress amplification, showing superior antitumor toxicity to disulfiram.